Pemanfaatan Media Sosial Untuk Peningkatan Daya Jual Produk UMKM - Muhammad Syafruddin; Syiar Rinaldi; Ishak Ishak; Andi Pattiware; Annas Lalo (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
This community service activity aims to provide understanding and knowledge for MSME players in using social media to help their businesses increase sales. This activity was carried out for one day and the method used was to start with a survey and continue with material presentation and discussion. The results of the activities carried out provide several strategies for utilizing social media such as Understanding the Market and Target Audience, Determining the Right Platform, Attractive Business Profile, Quality Content, Consistent Posting Schedule, Using Interactive Features, Special Promotions and Discounts, Collaborating with Influencers or Customers, Performance Analysis and Effective Customer Service. For further activities, mentoring activities need to be added to further assist the actors in implementing the strategies provided.